Additions to the taxonomy of the genus Ophionea Klug, 1821 (Coleoptera: Carabidae: Lebiinae) and a new species from India - Anagha, V. S. Sudhakar; Sabu, Thomas K. (Zootaxa, 2024)
A new ground beetle species Ophionea vvrei sp. nov. is described from South India, with revised key to the species of the genus Ophionea, revised descriptions of O. bhamoensis bhamoensis (Bates, 1892) and O. interstitialis Schmidt-Göbel, 1846, first report of Ophionea ceylonica (Baehr, 1996) from Indian mainland and designation of the lectotype of O. indica (Thunberg, 1784).